On the Tragedy of Mass Shooting: the Crime Effects - Christian Gunadi (Global Labor Organization (GLO), 2021)
Recent years have seen a rise in mass shooting incidents in the United States. While direct victims and their families undoubtedly suffer the most serious consequence of mass shootings, little is known on whether mass shootings have negative impacts beyond those immediately exposed to the incidents. In this paper, I examine the crime consequences of mass shootings. I hypothesize that mass shootings can increase crimes through its adverse effects on local labor market conditions. Utilizing difference-in-differences strategy that exploits geographic and temporal variation in mass shooting incidents across U.S. counties, the results of the analysis suggest that mass shooting incident is associated with a rise in crimes, especially those carried out for monetary gains. The most conservative estimate indicates that mass shooting incident increases the overall property crime rate by about 4%.
Keywords: K42; H23; D84; J18; 330; Mass Shootings; Violence; Crime; Economic Outlooks